Does financial agglomeration promote the green development in China? A spatial spillover perspective. (10th November 2019) - Yuan, Huaxi; Zhang, Tianshu; Feng, Yidai; Liu, Yaobin; Ye, Xinyue
Abstract: The role of financial agglomeration in China's green development has generated many fascinating debates for scholarly research, but few studies have considered environmental effects of financial agglomeration from the spatial spillover perspective. Taking both natural and socio-economic factors into accounts, this paper explores the interaction between financial agglomeration and green development using the panel data of 285 prefecture-level Chinese cities from 2003 to 2015. The results show that both financial agglomeration and green development have demonstrated a trend of spatial convergence. Secondly, financial agglomeration can promote the green development of both focal and surrounding cities. Thirdly, financial agglomeration is conducive to enhance regional green development level in Western China, while only Eastern and Central China witness significant spatial spillover effects. Fourthly, the direct effect of financial agglomeration on green development at the city level exists, whereas megacities and large cities witness a significantly adverse spatial spillover effect. This paper also presents policy recommendations.